By the Proprietary and Governour of the province of Pensilvania and territories thereunto belonging with advise of his council, a proclamation : given ... at Philadelphia the sixth day of the first month in ... 1700/1.
January 6, 1701 Proclamation of Governor William Penn regarding the prorogation of the General Assembly from February 1st to April 1st. Of note, the governor determined that there was no pressing business for the legislature, but did not dissolve the assembly, as this action would trigger elections which would cause a delay should an emergency arise.